Pokora – sekret serca Maryi w ujęciu papieża Franciszka - Wojtczak, Adam (Poznańskie Studia Teologiczne, 2022)
In the modern world, where humility does not enjoy much esteem, Francis takes up the motif of Mary’s humility. He maintains that She is the most humble among all creation. This is the secret of Her heart. Mary’s beauty and success result not only from the fullness of grace bestowed upon Her by God, but also from the fact that She did not focus on Herself or admire Herself but instead She turned to God and neighbours. The article looks closely at Mary’s humility according to Pope Francis in order to discover the originality of his interpretation. It is composed of three points. The first one addresses the question of why Mary’s humility drew God’s attention. The second point presents basic features and manifestations of Mary’s humility. The third point brings to light a model nature of Mary’s humility, that is in what sense She is a “golden rule” for Christians. At the end of the article conclusions are presented. They point out that Francis’s approach to Mary’s humility is somewhat different from the common approach, because he sees in it not only an attribute of faith, but for him it is a point of departure and the origin of faith. The Pope’s reflections are of theological and pastoral nature, because he is focused on Christian practice. He assumes that our following Mary’s humility will oppose dangerous spiritual worldliness and will considerably contribute to creating ‘new humanism’.